Multi-tissue Multi-omics Systems Biology to Dissect Complex Diseases - Yang, Xia (Trends Mol Med, 2020)
Most complex diseases involve genetic and environmental risk factors, engage multiple cells and tissues, and follow a polygenic or omnigenic model depicting numerous genes contributing to pathophysiology. These multidimensional complexities pose challenges to traditional approaches that examine individual factors. In turn, multi-tissue multi-omics systems biology has emerged to comprehensively elucidate within- and cross-tissue molecular networks underlying gene-by-environment interactions and contributing to complex diseases. The power of systems biology in retrieving novel insights and formulating new hypotheses has been well-documented. However, the field faces various challenges that call for debate and actions. In this opinion, I discuss the concepts, benefits, current state, and challenges of the field, and point to the next steps towards network-based systems medicine.